Prevalence and factors of adherence to post exposure follow-up among sharps-injured healthcare workers in a government hospital - Abdullah Aliff Abdul Wahab,; Faiz Daud,; Rosnah Ismail,; Azmi Mohd. Tamil, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Adherence to post-exposure follow-up protocol reflects the continuity of care in managing sharps injuries among healthcare workers (HCWs). This study aimed to determine the prevalence of adherence to post-exposure follow-up and its associated factors in a public hospital. This cross-sectional study was conducted at Hospital Melaka, Malaysia. All 250 reported sharps injury cases among HCWs were conveniently sampled throughout the period of five years between 2013 to 2017. Data from the Infectious Disease Clinic were extracted and analysed descriptively via multivariate binary logistic regression using IBM SPSS version 22 software. Sharps-injured HCWs were predominantly female (64.4%) with a median age of 26 (IQR 24 to 28) years old, had two years or more of experience (36.8%), status was negative for HIV/HBV/HCV (68.4%) and non-paramedics (84.4%). The prevalence of adherence to follow-up was 36.8%. Paramedics were more adhere to follow-up (56.4%) than the non-paramedics group. The factors that were significantly associated with follow-up adherence were the type of device (p=0.049) and occupation category (p=0.006). Paramedics had 2.66 times the odds of adherence to post-exposure follow-up compared to non-paramedics (95%CI: 1.32, 5.36; p = 0.006) when adjusted for type of devices. Based on our study, paramedics showed a good example of HCWs with a higher prevalence of adherence as compared to non-paramedics. However, the overall prevalence of adherence was still low. Hence, further research on finding the determinants of adherence in a local setting is undoubtedly needed.